2016
DOI: 10.1016/j.socscimed.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to “race equality” in the English National Health Service: Insights from the healthcare commissioning arena

Abstract: Inequitable healthcare access, experiences and outcomes across ethnic groups are of concern across many countries. Progress on this agenda appears limited in England given the apparently strong legal and policy framework. This disjuncture raises questions about how central government policy is translated into local services. Healthcare commissioning organisations are a potentially powerful influence on services, but have rarely been examined from an equity perspective. We undertook a mixed method exploration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 19 publications
2
47
2
1
Order By: Relevance
“…Within this population access to, and outcomes from, mental health care are not currently equitable (Sproston and Nazroo, 2002). There is evidence of professional uncertainty among practitioners about how to engage with ethnic and religious diversity (Kai et al, 2007), and concerns about inequitable provision among commissioners (Salway et al, 2016). Among minority ethnic clients, research highlights low levels of trust in mental health services and widespread failure to accommodate spiritual needs in National Health Service (NHS) care (Mir and Sheikh, 2010;NICE, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Within this population access to, and outcomes from, mental health care are not currently equitable (Sproston and Nazroo, 2002). There is evidence of professional uncertainty among practitioners about how to engage with ethnic and religious diversity (Kai et al, 2007), and concerns about inequitable provision among commissioners (Salway et al, 2016). Among minority ethnic clients, research highlights low levels of trust in mental health services and widespread failure to accommodate spiritual needs in National Health Service (NHS) care (Mir and Sheikh, 2010;NICE, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We identi ed 2166 references, scanned 133 titles and abstracts and retrieved 42 publications for full texts. From these, we included six studies (including a total of 1155 participants) that reported data on clinical commissioning and health inequalities [46][47][48][49][50][51] and excluded 36 studies (Additional le 2). Of the six, four were qualitative.…”
Section: Resultsmentioning
confidence: 99%
“…Of the six, four were qualitative. [46][47][48][49] All studies were conducted between 2010 and 2017 and the list of included studies is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…This may be a consequence of the challenges faced in undertaking such research or to the lack of priority of immigrants’ health in research policies. Decision makers have highlighted the lack of data and paucity of relevant evidence as reasons for not starting interventions that specifically target immigrants 21 . Therefore, we have formulated a set of recommendations (table 2) informed by our analysis of the existing evidence base, which we address in greater detail below.…”
Section: Discussionmentioning
confidence: 99%